Vivax malaria: neglected and not benign. - Price, R; Tjitra, E; Guerra, C; Yeung, S; White, N; Anstey, N (2007)
Plasmodium vivax threatens almost 40% of the world's population, resulting in 132-391 million clinical infections each year. Most of these cases originate from Southeast Asia and the Western Pacific, although a significant number also occurs in Africa and South America. Although often regarded as causing a benign and self-limiting infection, there is increasing evidence that the overall burden, economic impact, and severity of disease from P. vivax have been underestimated. Malaria control strategies have had limited success and are confounded by the lack of access to reliable diagnosis, emergence of multidrug resistant isolates, the parasite's ability to transmit early in the course of disease and relapse from dormant liver stages at varying time intervals after the initial infection. Progress in reducing the burden of disease will require improved access to reliable diagnosis and effective treatment of both blood-stage and latent parasites, and more detailed characterization of the epidemiology, morbidity, and economic impact of vivax malaria. Without these, vivax malaria will continue to be neglected by ministries of health, policy makers, researchers, and funding bodies.